Overlap of bullous, anti-laminin-332, and anti-p200 pemphigoid with concomitant anti-contactin-1-positive inflammatory polyneuropathy treated with intravenous immunoglobulins as a manifestation of epitope spreading - Wald, Alexander; Toberer, Ferdinand; Gutschalk, Alexander; Enk, Alexander; Hoffmann, Jochen (JAMA dermatology, 2019)
This case report describes a patient who experienced bullous, anti-laminin-332, and anti-p200 pemphigoid with concomitant anti-contactin-1-positive inflammatory polyneuropathy treated with intravenous immunoglobulins as a manifestation of epitope spreading.
Gesehen am 27.09.2019